2016
DOI: 10.1111/ijcp.12872
|View full text |Cite
|
Sign up to set email alerts
|

Faces of all clinically engaged staff: a quality improvement project that enhances the hospitalised patient experience

Abstract: The FACES instrument improved patients' recognition of providers' names and roles, as well as patients' perception of inter-provider teamwork. There was a non-significant trend towards improved satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…roles was positive in 8 of 10 studies that measured the outcome. 15,22,[25][26][27][28]31,33 The impact of visual tools on patient-provider communication was positive in 4 of 5 studies. 24,28,29,32 The influence of visual tools on patient satisfaction with care was measured in 8 studies; of these, 6 studies reported a positive impact.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…roles was positive in 8 of 10 studies that measured the outcome. 15,22,[25][26][27][28]31,33 The impact of visual tools on patient-provider communication was positive in 4 of 5 studies. 24,28,29,32 The influence of visual tools on patient satisfaction with care was measured in 8 studies; of these, 6 studies reported a positive impact.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies assessed the effect of visual tools on patients' understanding of provider roles. 13,14,22,26,27,33 Four studies reported a positive effect with the use of pictures, 27,33 whiteboards, 22 and patient portals. 26 However, 2 studies reported either no difference or negative impressions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an effort to improve the hospital experience and patient satisfaction, some institutions have used photo "trading cards" to help patients identify their physicians. Studies show that patients frequently have difficulty identifying their hospital care team members and the use of trading cards can improve recognition [1][2][3][4][5][6]. Additionally, a randomized controlled trial by Brener et al found this also improved impressions of teamwork effectiveness [1].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that patients frequently have difficulty identifying their hospital care team members and the use of trading cards can improve recognition [1][2][3][4][5][6]. Additionally, a randomized controlled trial by Brener et al found this also improved impressions of teamwork effectiveness [1]. Other studies have demonstrated that patients believe their ability to identify their physicians facilitated both trust and satisfaction [5,7,8].…”
Section: Introductionmentioning
confidence: 99%